Reminiscing Coffee Culture in Adaptive Reuse Coffeeshop in Heritage Building, Euphoria or Sustainable? - Savitri, Mila Andria; Santosa, Imam; Junaidy, Deny Willy; Maharani, Yuni (Syntax Corporation, 2026)
Coffee culture in Indonesia has progressively evolved into an urban lifestyle nowadays. The rapid growth of coffee shops aligns with Indonesia’s position as one of the world’s top five coffee-producing nations. Coffee consumption has surged by up to 250% through years 2014-2021 (International Coffee Organization,2021) and coffeeshops grew from 1083 to 2937 shops in 2016-2019. Amidst the pressures of urban development, land scarcity and evolving needs of contemporary society concerns, a paradigm shift has emerged, suggesting that commercial functions like coffee shops could repurpose old buildings, including heritage ones, instead of constructing anew. The adaptation of these structures merely known as adaptive reuse approach. However, the awareness among users regarding the importance of sustainable development, particularly in environmental, social, cultural, and economic aspects, remains a question. Is this trend a transient phase or a lasting shift in consciousness? This article reviews theories related to adaptive reuse, the growth of coffee shops within heritage buildings, and user perceptions of adaptive reuse coffee shops, with case study in Bandung City. Employing literature review, field observations, and questionnaire distributed to 99 participants, this study aims to ascertain consumers’ understanding of adaptive reuse concepts and how it influences consumers reasons for visiting these coffee shops. In conclusion, this study contributes to understanding consumer awareness of adaptive reuse in coffee shops and how this approach impacts consumer motivation visit. It sheds light on the evolving landscape of sustainable urban development within the context of cultural heritage and consumption lifestyle trends.